Maternal morbidity and mortality: an iceberg phenomenon. (23rd September 2021) - Leitao, S; Manning, E; Greene, RA; Corcoran, P; ,
Abstract : Objective: To apply the iceberg model, quantifying absolute and relative incidence, to the four main causes of maternal morbidity and mortality in Ireland: haemorrhage, hypertension, sepsis and thrombosis. Design: Secondary analysis of national data on maternal morbidity and mortality. Setting: Republic of Ireland. Population or sample: Approximately 715 000 maternities, 1 200 000 maternal hospitalisations, 2138 cases of severe maternal morbidity (SMM) and 54 maternal deaths. Methods: Incidence rates and case‐fatality ratios were calculated. Main outcome measures: Maternal death, SMM and hospitalisation. Results: At the 'tip of the iceberg', the incidence of maternal death per 10 000 maternities was 0.09 (95% CI 0.03–0.20) due to thrombosis and 0.03 (95% CI 0–0.11) due to haemorrhage, hypertension disorders or sepsis. For one death due to thrombosis there were 35 cases of pulmonary embolism and 257 thrombosis hospitalisations. For one death due to eclampsia, there were 58 eclampsia cases, 13 040 hospitalisations with pre‐existing hypertension and 40 781 hospitalisations with gestational hypertension. For one death due to pregnancy‐related sepsis, there were 92 cases of septicaemic shock and 9005 hospitalisations with obstetric sepsis. For one maternal death due to haemorrhage, there were 1029 cases of major obstetric haemorrhage and 53 715 maternal hospitalisations with haemorrhage. For every 100 maternities, there were approximately 16 hospitalisations associated with haemorrhage, 12 associated with hypertension disorders, three with sepsis and 0.2 with thrombosis. Conclusions: Haemorrhage and hypertension disorders are leading causes of maternal morbidity in Ireland but they have very low case fatality. This indicates that these morbidities are managed effectively but their prevention requires more focus. Tweetable abstract: Study shows that haemorrhage and hypertension are main causes of #maternalmorbidity in Ireland. Timely interventions for #maternalhealth and focus on prevention of severe and non‐severe morbidities are needed. @NPEC #maternityservices #clinicalaudit #qualityimprovement. Tweetable abstract: Study shows that haemorrhage and hypertension are main causes of #maternalmorbidity in Ireland. Timely interventions for #maternalhealth and focus on prevention of severe and non‐severe morbidities are needed. @NPEC #maternityservices #clinicalaudit #qualityimprovement.